The optimization of leased line distribution at the EDGE of local access network via WAN convergence network - Nor Shahniza Kamal Bashah; Nor Haizon Husin; Syaripah Ruzaini Syed Aris; Norjansalika Janom; Noor Habibah Arshad (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Managing the multiple services of the leased line at the same location is quite critical especially when the resource become highly utilized. Bundling the several network resource components into a one box by simplifying the multiple networks to a single network can help to reduce the utilization of network resources. This paper presents a study on optimiziation of leased line distribution at the EDGE of Local Access Network via WAN convergence network. In this study, a WAN Convergence Network is designed which intends to use only a single leased line network in a location rather than multiple leased lines. It is using a simple concept of SDH structured which channelized the time slots and control the transmission line. The time slots will be relocated from the multiple leased lines into a WAN Convergence Network and it will be de-multiplexed through the Data Circuit Terminating Equipment (DCE) at the customer premises. The WAN Convergence Network design starts from the Digital Data Network (DDN) until the DCE which includes the Local Access Network. This approach will be able to save the network resource especially the time slots, cable port, DCE and consequently avoid adding new network infrastructure. This research will result to the new network design which offer multiple leased line networks at the customer end by using only one dedicated leased line network namely WAN Convergence Network.